On linearization techniques for budget-constrained binary quadratic programming problems - Yang, Mei-Jia; Xia, Yong; Zou, Hui-Min (Operations research letters, 2016)
Glover’s linearization technique is revisited for solving the binary quadratic programming problem with a budget constraint (BBQP). When compared with the recent two linearizations for (BBQP), it not only provides a tighter relaxation at the root node, but also has a much better computational performance for globally solving (BBQP).